Capacity Building of Village Apparatus through Training Needs Analysis in Cibunar Village, Tarogong Kidul District, Garut Regency - Setiadi, Ade; Kania, Ikeu; Akbar, Gugun Geusan (Jurnal Ekuisci, 2025)
Background. In an era that continues to develop, village officials are expected to be able to follow the flow of change that includes the dynamics of government regulations, information technology advancements, and social transformation in the community. Their duties now focus not only on the administrative aspect but also include essential roles as quality public service providers, transparent financial managers, and drivers of citizen participation in the village development process. Aims. The research titled Enhancing the Capabilities of Village Apparatus through Training Needs Analysis in Cibunar Village, Tarogong Kidul District, Garut Regency aims to identify key areas of training essential for improving the effectiveness of village officials in handling administrative functions and delivering quality public services. Methods. This study is grounded in realizing that village autonomy, as outlined in the Village Law, demands qualified and adaptable human capital. Using a descriptive qualitative approach, data were gathered through in-depth interviews and participatory observation involving village leaders selected based on their relevance and roles. Result. The study found that the most pressing training needs include administrative skills, the integration of technology, and communication proficiency, with administrative and technological competencies ranked as top priorities. The training needs were assessed across three main aspects: organizational structures, job-related responsibilities, and individual skillsets. This comprehensive method provides a solid framework for designing practical and targeted training initiatives. Conclusion. The study concludes that training programs tailored to the actual challenges faced in the field can significantly improve the performance of village apparatus. Implementation. These outcomes support evidence-based policy-making and enhance local governance, especially in pursuing sustainable and adaptive administrative systems.